Carboplatin plus Paclitaxel in the First Line Therapy of Recurrent and Advances Endometrial Cancer - Hamid Attarian (International Journal of Hematology-Oncology and Stem Cell Research, 2009)
Introduction: To evaluate the efficacy and safety of Carboplatin plus Paclitaxel in patients with advanced locoregional recurrence and metastatic endometrial cancer. Patient and Method: 32 eligible patients (median age 62, range 41-72) with measurable endometrial cancer were treated with Carboplatin (AUC= 6) and Paclitaxel (175 mg/m3) every 4 weeks for 6 cycles, or, until disease progression or severe toxicity. Result: The ORR was 54% (16 out of 30), CR in 4 and PR in 12. The median progression free survival was 8.2 months. The 6 months overall survival was seen in 80% of trhe patients. The toxicity was generally tolerable. Conclusion: The combination of Carboplatin plus Paclitaxel was well tolerated in this trial. This regimen demonstrated feasible success in curing advanced endometrial cancer compared to other combination therapies used before (in terms of RR and toxicity).